The Features Of The English Language Variety Spoken By The Malacca Babas - Ong Chuan, Lee (Pusat Pengajian Ilmu Kemanusiaan, 1983)
This academic exercise has been written in five chapters. Chapter One deal with the rationale and aims of this study, the nature and method of data collection as well as the methodology used in the analysis of the data. A brief account of the informants who participated in this study is also given in the chapter.